Parents’ willingness to pay for COVID-19 vaccination for children in Malaysia using the contingent valuation method - Rajamoorthy, Yogambigai; Wagner, Abram L.; Kumaran, Vikniswari V.; Munusamy, Subramaniam; Taib, Niazlin M.; Tin, Ong H.; Bradin, Aaron; Vo, Trung Q. (Narra Sains Indonesia, 2023)
Children are susceptible and a potential source of transmission for coronavirus disease 2019 (COVID-19). However compulsory COVID-19 vaccination programs among children have not been a focus in Malaysia. The aim of this study was to measure parents’ willingness to pay (WTP) for the COVID-19 vaccine and analyze the effects of socioeconomic variables on parents’ WTP. An online cross-sectional study was conducted in Malaysia with two waves of surveys (i.e., different samples for each wave), March and June 2021. The study participants were Malaysian parents above 18 years old. Parents were randomized between two vaccine effectiveness profiles (95% and 50% effectiveness) and two risk levels of an adverse event (5% and 20% risk of fever). The WTP was estimated using a double-bounded dichotomous choice. Socioeconomic variables such as age of parent, gender, insurance, income, and education were examined. A total of 292 parents in March 2021 and 271 in June 2021 were included in the study. The vaccine safety and effectiveness profile did not significantly impact the WTP. In March 2021, the estimated WTP ranged from RM344.74 to RM399.64 (US82.5 to US95.6) across vaccine profiles and between RM377.55 and RM444.33 (US90.3 to US106.3) in June. Insurance status was associated with the parents’ WTP, and during the June wave, the age of parents influenced the WTP. Implementing subsidies or free vaccinations is considerable to increase herd immunity and prevent transmission of COVID-19 in Malaysia.